Determination of genetic sources of some alfalfa tax a (Medicago sativa L.) cultured in Turkey - Sancar, Pelin Yilmaz; Demirpolat, Azize; Cacan, Erdal (Parlar Scientific Publications, 2021)
The aim of this study, was to determine the genetic proximity and distances of Medicago sativa species and to identify phylogenetic interrelationships using the sequence analysis information of the non-coding "?r« and ITS" region in the chloroplast genome of the Medicago sativa species in Turkey. A phylogenetic systematic study was carried out to determine the genetic origins of the populations belonging to the species by using the molecular data of the Medicago sativa species grown in Bingol. A total of 39 alfalfa fields were visited, including 12 villages in the Bingol plain, and a neighborhood connected to the provincial center. As a result of the sequence reading, the genetic mapping of the local alfalfa genotypes was obtained (the local alfalfa was obtained). The populations of this species were collected from 12 different regions cultivated in the Bingol province and 36 individuals were included in the analysis. The base sequences of the obtained regions were analyzed and their genetic characteristics were compared, and then information was obtained about the proximity and the distance of the taxa from each other. This study is important in terms of being the first molecular based systematic study involving various populations of Medicago sativa cultivated in Bingol province. © 2021 Parlar Scientific Publications. All rights reserved.
Keywords: CpDNA trnL3'-trn¥ region; Medicago sativa; Molecular phylogeny; PCR; R-DNA ITS